MiR-128 promoted adipogenic differentiation and inhibited osteogenic differentiation of human mesenchymal stem cells by suppression of VEGF pathway. (4th May 2017) - Zhang, Wen; Yao, Chen; Wei, Zhanying; Dong, Qirong
Abstract: Context: MicroRNA-128 (miR-128), a brain-enriched microRNA, has been reported to participate in the regulation of cell differentiation, but its potential roles in adipogenic and osteogenic differentiation of human mesenchymal stem cells (hMSCs) have not been addressed. Objective: The study was conducted to investigate the effects and mechanism of miR-128 on adipogenic and osteogenic differentiation of hMSCs. Materials and methods: Morphology of hMSCs, lipid droplets and calcium nodules were observed and photographed by LSM microscopy. Expression of CCAAT/enhancer binding protein-α (C/EBPα), peroxisome proliferator-activated receptor-γ (PPARγ), miR-128, vascular endothelial growth factor (VEGF), osteocalcin (OCN) and Runt-related transcription factor 2 (RUNX2) was determined by RNA preparation and reverse transcription polymerase chain reaction (RT-PCR), protein expression of VEGF was analyzed by Western blot. Results: It was suggested that miR-128 expression showed a 4.56-fold induction by adipogenic treatment and a 58.8% reduction by osteogenic treatment. Over-expression of miR-128, promoted adipogenic differentiation while inhibited osteogenic differentiation. In contrast, adipocyte formation was inhibited and osteogenesis was enhanced in cells slicing miR-128. Furthermore, over-expression of miR-128 down-regulated VEGF expression in adipogenically and osteogenically differentiated cells. We further identified VEGF as a key regulator in miR-128-induced adipogenic and osteogenic differentiation. Following knockdown of VEGF, the effects of over-expression of miR-128 on adipogenic and osteogenic differentiation of hMSCs were limited. Conclusion: It was indicated that miR-128 could regulate adipogenic and osteogenic differentiation of hMSCs significantly through the suppression of VEGF pathway.